2022
DOI: 10.3390/molecules27227893
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and COVID-19

Abstract: Herbal products are a major source of herbal medicines and other medicines. Essential oils have shown various pharmacological activities, such as antiviral activity, and therefore are proposed to have potential activity against SARS-CoV-2. Due to their lipophilicity, essential oils can easily penetrate the viral membrane and cause the viral membrane to rupture. In addition, crude essential oils usually have many active constituents that can act on different parts of the virus including its cell entry, translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 103 publications
0
9
0
2
Order By: Relevance
“…Therefore, natural compounds in herbs seem to be rich sources for screening potential drugs against coronaviruses. As expected, several herbal medicines as well as isolated compounds in herbs have been reported to possess inhibitory activities against SARS-CoV-2 in the past few years [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Although herbal medicines and their isolated compounds are not as effective as chemical antiviral drugs, they are empirically safe for the human body, particularly after long-term consumption.…”
Section: Introductionmentioning
confidence: 61%
“…Therefore, natural compounds in herbs seem to be rich sources for screening potential drugs against coronaviruses. As expected, several herbal medicines as well as isolated compounds in herbs have been reported to possess inhibitory activities against SARS-CoV-2 in the past few years [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Although herbal medicines and their isolated compounds are not as effective as chemical antiviral drugs, they are empirically safe for the human body, particularly after long-term consumption.…”
Section: Introductionmentioning
confidence: 61%
“…During the coronavirus crisis, food supplements such as malate and citrate salts and vitamin C, Zn, Cu, Ca, Mg, and K have proven to have positive effects on the body's metabolism by reducing blood acidity and thus boosting immunity, for example, plants' malate and citrate are metabolized into HCO 3 − ; vitamin C is an essential component for collagen synthesis in osteoclasts. [ 61,140,141 ]…”
Section: Discussionmentioning
confidence: 99%
“…During the coronavirus crisis, food supplements such as malate and citrate salts and vitamin C, Zn, Cu, Ca, Mg, and K have proven to have positive effects on the body's metabolism by reducing blood acidity and thus boosting immunity, for example, plants' malate and citrate are metabolized into HCO 3 − ; vitamin C is an essential component for collagen synthesis in osteoclasts. [61,140,141] • Which is better, staying at home and breathing nonfresh air, or staying in a garden and breathing fresh air, or staying on the beach? One way to increase the oxygen content of our bodies is to breathe in fresh air, in particular, the ozone before sunrise, which clears acidosis and restores the alkaline state and supports the exhausted immunity.…”
Section: Role Of Blood Grouping and Transfusion In Covid-19 Infectionmentioning
confidence: 99%
“…Molecular modeling is an interesting in silico tool used to determine the stability of compounds and the interaction types responsible for antiviral biological activity. Different EO studies revealed antiviral activity against SARS-CoV-2 [ 29 , 30 , 31 ]. Two different software were used: Surflex-Dock and UCSF chimera in UCSF Chimera 1.13.1 [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%